Marty McGuire - Messner, Kate.; Floca, Brian (New York : Scholastic Press, 2011)
When tomboy Marty is cast as the princess in the third-grade play, she learns about improvisation, which helps her become more adaptable.
M
b
M
Keywords: Theater -- Fiction; Schools -- Fiction